North of Boston: Models of Identity, Subjectivity and Place in the Poems of Robert Frost - Regan, Stephen (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractAlthough the titles of Robert Frost’s collections of poetry, including North of Boston, appear to ground his work in a precise location and a known community, the poems themselves belie any secure sense of geography and any secure sense of attachment. Many of the poems were, in fact, composed in Buckinghamshire and Gloucestershire shortly before the outbreak of the First World War, and they reveal an acute awareness of British, as well as American, literary traditions and ideals. This essay looks at how Frost created the New England of his poems, subtly establishing lines of continuity with British and American Romanticism while simultaneously harbouring profound philosophical doubts about inherited models of poetic subjectivity and imagination. The place of poetry, for Frost, is seen to be a place in which the play of mind is, itself, the most pressing subject matter.